Good Corporate Governance and Value of Property and Real Estate Companies on the Indonesian Stock Exchange - Anisah Iriyani Siti Mudaifah (Faculty of Business and Economics , Universitas Yapis Papua, 2024)
This research aims to determine the effect of good corporate governance on company value by taking case studies of Property and Real Estate companies listed on the IDX during the 2019-2023 period. This type of research uses a quantitative approach with multiple linear regression analysis methods using the e-views version 12 program. The samples taken used purposive sampling techniques and amounted to 90 sample data. This research shows that the audit committee and institutional and managerial ownership positively influence company value. In contrast, the independent board of commissioners does not affect company value. The audit committee, institutional ownership, managerial ownership, and independent board of commissioners can explain the company value at 31.56%.